Humanismo crítico no cinema de Pedro Almodóvar: análise de linguagem e narrativa - Luiza Aguiar Leite (2010)
This study aims to demonstrate how Almodóvar takes the viewer to enter the motivations of the behaviors considered marginal by society. Is an attempt to understand the ability of the Spanish filmmaker tackling controversial issues, opening up possible spaces for humanistic interpretations deeper, even in extreme situations highly controversial. Almodóvar uses the cinematic language to reveal the secrets of his characters, leading the viewer to position itself differently from the common, abolishing the old moralistic dichotomy between the good and bad, "especially in light of attitudes that are often regarded as mere fruit aberration, solitude and madness. Instead, Almodovar always see his characters in a highly problematic human content, even under compromising appearances or abject.